Combining passive and active restoration to rehabilitate a historically polluted marine site - Bianchelli, Silvia; Martini, Francesco; Lo Martire, Marco; Danovaro, Roberto; Corinaldesi, Cinzia (Frontiers in Marine Science, 2023)
Introduction Passive and active restoration approaches have been often considered as different alternatives to achieve the ecological restoration of a degraded site. This false dichotomy has been overcome in terrestrial ecosystems, for which a range of restoration approaches have often been applied within the same restoration project, creating a continuum of interventions. In the marine environment, the combined approach based on passive and active restoration is less studied. Methods Here, we tested the possibility of actively restoring a macroalgal population in a historically polluted industrial site, subjected to decadal passive restoration (i.e., unassisted, or spontaneous recovery following cessation of industrial activity), in the Mediterranean Sea. Recently, it has been demonstrated that in the site under scrutiny, there is no longer any sign of the historical contamination or impact on benthic fauna therefore the environmental conditions are indistinguishable from surrounding non-impacted areas. We used artificial breakwater barriers already present in the site to restore a population of the brown algae Gongolaria barbata. The intervention was conducted by applying an in situ recruitment approach and a complementary action using cages to exclude the herbivores. The G. barbata recruits were transplanted on the artificial reefs and after they reached the maximum growth inside the cages, one cage was opened and another one was completely removed to also test the grazing pressure. The associated benthic assemblages were also analysed in terms of meio- and macrofaunal abundance, the richness of taxa, and taxonomic composition. Results and discussion Our results indicate that, at least over a relatively short period (i.e., 6 months), the use of the cages represents a useful tool to let the macroalgae grow enough to counterbalance the herbivory pressure. The associated fauna below the macroalgae was characterized by a different taxonomic composition when compared to controls (i.e., artificial reefs without the macroalgae), particularly when considered the rare taxa. In conclusion, the combination of passive and active restoration can be considered a useful approach to restore marine sites degraded by historical industrial activities.